POLA KOMUNIKASI INTRABUDAYA DAN PERKAWINAN NYEROD DALAM MASYARAKAT HINDU DI BALI - Ni Putu Limarandani; Anak Agung Ketut Patera; Untung Suhardi (Institut Agama Hindu Negeri Gde Pudja Mataram, 2020)
This study focused to address research namely; phenomena marriage nyerod in interaction symbolic and construction identity Balinese women. The subject matter is present the communication interculture the community Hindu Bali about the marriages nyerod. A method of using qualitative analysis, but the result of this research is the presence of the Hindu religious Bali cannot be separated from culture Bali itself. The disappearance of existence Hinduism Bali it can be ascertained culture bali will disappear, given that almost all activities associated with culture Bali ngayah in the concept of religious activities. Of a mutual relation communication of intra culture in the context of the community Bali work, when the identity of the us culture and social identification fused and become part of the process of the decision of stakeholders and adat experts in local customs Bali. Social position stakeholders and indigenous experts in local customs so startegis, as well as to determine like patron client relationship the who works. In such a position as, the customs and religion a concept one, when things coalesce in ourselves a stakeholders customary. Inter relations culture this is what consciously have built relation chair in society Hindu Bali, including on the deeply private such as marriage, when indigenous go in until in domain so personal in the life of someone